Pertanggungjawaban Pidana Penyelenggara Pemilu Atas Penggunaan Diskresi dalam Kondisi Stagnasi Penyelenggaraan Pemilu (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Discretion exercised by election management bodies constitutes an administrative instrument that is functionally necessary to prevent stagnation in electoral processes under conditions of legal vacuum, normative ambiguity, or extraordinary circumstances. However, in practice, discretionary decisions often generate public concern and expose election officials to the risk of criminalization, particularly when such discretion is assessed through a formalistic and result oriented criminal law paradigm. This study aims to analyze the construction of criminal liability of election administrators for the use of discretion in conditions of electoral stagnation, by examining the paradigm shift from the old Indonesian Criminal Code to the new Criminal Code and its implications for criminal law enforcement under the Criminal Procedure Code. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings reveal that the old Criminal Code tended to facilitate policy criminalization by emphasizing formal violations and objective consequences, whereas the new Criminal Code introduces a substantive approach centered on subjective fault, official purpose, and rationality of action. Nevertheless, the lack of synchronization with the Criminal Procedure Code which remains focused on conventional evidentiary standards causes discretionary actions of election administrators to remain legally ambiguous. Therefore, harmonization between substantive criminal law and criminal procedure law, along with a transformation in law enforcement reasoning, is essential to ensure that discretion exercised by election officials is assessed proportionally, contextually, and in line with democratic principles.